Morphological effects of neem (Azadirachta indica A. Juss) seed oil with known azadirachtin concentrations on the oocytes of semi-engorged Rhipicephalus sanguineus ticks (Acari: Ixodidae) - Remedio, R. N. [UNESP]; Nunes, P. H. [UNESP]; Anholeto, L. A. [UNESP]; Oliveira, P. R. [UNESP]; Camargo-Mathias, M. I. [UNESP] (Springer, 2015)
The concern about the harmful effects caused by synthetic pesticides has led to the search for safe and ecological alternatives for pest control. In this context, the neem tree (Azadirachta indica) stands out due to its repellent properties and effects on various arthropods, including ticks. For this reason, this study aimed to demonstrate the potential of neem as a control method for Rhipicephalus sanguineus ticks, important vectors of diseases in the veterinary point of view. For this, R. sanguineus semi-engorged females were subjected to treatment with neem seed oil enriched with azadirachtin, its main compound, and ovaries were assessed by means of morphological techniques in conventional light microscopy, confocal laser scanning microscopy, and transmission electron microscopy. Neem demonstrated a clear dose-dependent effect in the analyzed samples. The observed oocytes presented, especially in the groups treated with higher concentrations of neem oil, obvious signs of cytoplasmic disorganization, cellular vacuolization, nuclear and nucleolar irregularity, dilation in mitochondrial cristae, alterations in mitochondrial matrix, and swelling of rough endoplasmic reticulum. Intracellular microorganisms were observed in all analyzed groups, reinforcing the importance of ticks in the transmission of pathogens. A greater quantity of microorganisms was noted as the concentration of neem increased, indicating that the damaged oocytes may be more susceptible for their development. Such morphological alterations may promote future damages in reproductive performance of these animals and demonstrate the potential of neem seed oil for the control of R. sanguineus ticks, paving the way for new, cheaper, and safer methods of control.
Keywords: Control; Brown dog tick; Acaricide; Reproduction; Phytochemical